Impact of preoperative body mass index on the final outcome after laparoscopic sleeve gastrectomy for morbid obesity - Elbanna, Hosam (Ulus Cerrahi Derg, 2016)
OBJECTIVE: Laparoscopic sleeve gastrectomy (LSG) is a popular bariatric surgery due to its excellent results and limited morbidity. Our study aims to assess the efficacy of LSG in terms of loss of weight and co-morbidity improvement and to evaluate the impact of preoperative body mass index (BMI) on the final outcome. MATERIAL AND METHODS: The data of 173 patients who underwent LSG were analyzed. Laparoscopic sleeve gastrectomy was indicated only for patients with BMI >40. Mean postoperative BMI, co-morbidity improvement, operative data and complications, length of hospital stay and excess weight loss were evaluated and recorded. RESULTS: This study included 151 females and 22 males with a mean age of 37.6 years. Patients were divided into two groups according to their BMI (group I <50, group II >50). Mean preoperative BMI was 53.8 kg/m(2). Mean operative time was 120 minutes. Mean duration of hospital stay was 3.2 days. Mean postoperative BMI decreased to 47.3 kg/m(2) at 1 year. Excess weight loss was 43.1% at 6 months, 71.1% at 1 year, and 87.5% at 5 years. Group I showed a significantly shorter length of hospital stay, more improvement of laboratory parameters and more reduction in BMI as compared to group II. There was one mortality and six cases had gastric staple line leakage. CONCLUSION: Laparoscopic sleeve gastrectomy is an efficient treatment to achieve significant weight loss that is maintained up to 5 years of follow up, also it improves some of the obesity related co-morbidities. This beneficial impact of LSG appears to be significantly higher in patients with BMI <50.